Influence of pseudo-stem and kodo millet on quality parameters of paneer (Journal of Food and Dietetics Research, 2021)
Objectives: This study was performed to find out the effect of different types of food grade acids on the on the  quality of banana pseudo-stem (PS) powder and kodo millet (KM) flour incorporated paneer.  Material and Methods: Three different types of food grade acids such as citric acid, tartaric acid and malic acid  each at 2, 3, 4, and 5 percentage concentrations were added to assess the physiochemical, textural and organoleptic  parameters of banana pseudo-stem (PS) powder and kodo millet (KM) flour incorporated paneer.  Results: The moisture, protein, ash, yield, soluble, insoluble and total fiber of PSKM paneer increased with  the increasing strength of the food grade acid. However, the specified parameters for PSKM paneer made using  coagulants at 2, and 3 percent levels were statistically comparable (P > 0.05) except insoluble fiber content. Most of the  textural and sensory characters of the PSKM paneer decreased with increasing concentration of the food grade acid. The type of coagulant also showed variations in the majority of the constitutions of PSKM paneer. The KMF paneer  samples made with citric acid and tartaric acid had significantly higher (P < 0.05) values for moisture, protein, fat ash,  total yield, soluble fiber, insoluble fiber and total fiber than PSKM paneer made with malic acid at all concentrations.  No significant difference was seen in textural characteristics and sensory scores among all the samples.  Conclusion: Hence, to fabricate PSKM paneer with the majority desirable characteristics from pseudo stem  powder and kodo millet flour, it is recommended that citric acid and tartaric acid at 5 percent concentration can  be utilized as coagulants.
Keywords: Pseudo-stem; Kodo millet flour; Citric acid; Tartaric acid; Malic acid; Paneer